"Evidence of Me" Becoming "Evidence of Us": A Case Study of the Policy, Processes, Donor Relations and Responses of Selected New Zealand GLAM Institutions to Personal Donations of Collections and Artifacts. Issue 1 (8th February 2022) - Day, Alison S.; Krtalić, Maja
Abstract: Donors are important contributors to collection development in GLAM institutions, yet interactions and communications around policy and procedures with donors are under researched. Using a case study research design to investigate donor relationships nine participants from five New Zealand GLAM institutions were selected for interview. Participants were found to value their trust-based donor relationships, investing time into their continued development. A content analysis of donation webpages found differences between them, emphasizing the range of institutional views regarding website communication value. This research offers constructive insights into the processes and challenges selected New Zealand GLAM institutions face in managing personal donations.